Pemanfaatan Theodolite Digital Sebagai Upaya Peningkatan Keaktifan Siswa dalam Pembelajaran Pengelolaan Hutan - Yanuarius Seran Fahik (Program Studi Matematika, Universitas Timor, 2023)
This study aims to increase student activity in learning forest management by utilizing Digital Theodolite in class eleventh grade students of the Forest Rehabilitation and Reclamation Engineering Competency at Nibaaf State Vocational High School in the school year 2022/2023 that conducted by Vocational (Productive) Teachers. This research is an action research (action research). This research was conducted at SMK Negeri Nibaaf, with 17 students as research subjects. This research consists of 3 (three) stages, namely: preparation, implementation, and monitoring. The data collection technique in this study was by observation during the learning activities. The instruments for collecting monitoring data for this activity are questionnaires and documentation. The data obtained were analyzed using percentage techniques. The findings of this study indicate that by utilizing the Digital Theodolite it can increase the activity of Nibaaf State Vocational High School students in learning forest management in the odd semester of the school year 2022/2023. Analysis of the results of the monitoring instrument evaluating the results of learning activities achievement in quantitative terms is 89.43 % (category A = Very Good). The average achievement of Student Wellbeing (Student Happiness) before and after learning increased from 42.19 % to be 73.44 percent. (There was an increased 31.25%). Qualitative achievement is 72.19 % (Category B = Good).